Emigration and economic growth - KINDLEBERGER, C.P. (PSL Quarterly Review, 2014)
<!--[if gte mso 9]> 72 1024x768 <![endif]--> The paper considers the economic debate of whether emigration helps or hurts a country. This is a vital issue along the whole Mediterranean littoral from Portugal to Turkey. On one side of the debate emigration is regarded as the export of capital, inappropriate for poor countries. On the other side, it is considered to provide the benefits of getting unemployed or disguised unemployed to work. Here the arguments for and against emigration from developing countries is presented separately in static and dynamic terms. The focus is no intra-European South-North migration. It is shown that when conditions are right, large-scale migration can contribute to rapid growth in the country of immigration, based on greater supplies of labour, and in the country of origin, based on more effective resource allocation. It is argued that within certain limits emigration can be, and has been a positive force for growth in the South. JEL: O15 <!--[if gte mso 9]> Normal 0 14 <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->